(untitled) (ModaPalavra e-periódico, 2015)
The objective of this work is to see how art and fashion, represent the everyday in contemporary, especially with regard to the criticism of the current system, the representation of time trainer every day and appropriation of art by consumption. On the need for a methodological approach for the Arts also known as Wall Graffiti were chosen as a phenomenon of observation to be a public and easily accessible to most individuals who interact with the urban space art. It is observed that although the Art Wall is mostly a critique of the molds imposed by the system, it turns out to be bonded by it and transformed into consume high value goods.